Statistics demystified - Gibilisco, Stan (New York : McGraw-Hill, 2011)
This book is for anyone who has an interest in statistics and wants to learn more about it outside of a formal classroom setting. It can also be used by home-schooled students, tutored students, and those people wishing to change careers. The material is presented in an easy-to-follow way and can be best understood when read from beginning to end.
Includes bibliographical references and index.
Keywords: Statistics -- Popular works; Statistics -- Programmed instruction; Probabilities -- Popular works; Probabilities -- Programmed instruction